Fractional amplitude of low frequency fluctuation in drug-naïve first-episode patients with anorexia nervosa: A resting-state fMRI study - Lai, Jianbo (Medicine (Baltimore), 2020)
To characterize the fractional amplitude of low-frequency fluctuation (fALFF) in drug-naïve first-episode female patients with anorexia nervosa (AN) using resting-state functional magnetic resonance imaging (rs-fMRI). Whole brain rs-fMRI data were collected from 7 drug-naïve first-episode female patients with DSM-5 AN and 14 age-matched healthy female controls. fALFF values were calculated and compared between the two groups using a two-sample t test. Correlation analysis between the fALFF values in the entire brain and body mass index (BMI) was performed. Compared with the healthy controls, increased fALFF values were observed in the AN patients in their right hippocampus and left superior frontal gyrus, while decreased fALFF values were observed in their left rectus and left middle occipital gyrus. Moreover, low BMI was significantly associated with decreased fALFF in the left inferior frontal gyrus but increased fALFF in the left calcarine. In particular, the z-standardized fALFF (zfALFF) value of the left rectus was positive associated with BMI. Our findings suggest that spontaneous brain activity in the frontal region, hippocampus and rectus, characterized by fALFF values, was altered in drug-naïve, first-episode female patients with AN.